Pemberdayaan Guru Dalam Mewujudkan Madrasah Aman Bencana Melalui Pelatihan Membuat Media Komik Berbasis Mitigasi Bencana - Zuhroh, Ni’matuz; Zuhdi, Ahmad; Maimunah, Siti Annijat; Sari, Ulfi Andrian (JRCE (Journal of Research on Community Engagement), 2023)
Develop a pattern of empowerment with a series of systematic activities for class teachers at the Madrasah Ibtidaiyah (MI) level towards Disaster Safe Schools/Madrasah (SMAB) in South Malang Regency with high and very high levels of vulnerability to landslides. This service aims to provide training in the development of comic learning media based on landslide disaster mitigation. The service strategy uses CBR (Community-Based Research) by carrying out two stages, namely FGD and training to make comics using the pixton application. The location of the training is in two schools that are prone to landslides, namely MIN 1 Malang and MIN 3 Malang. The training carried out has been running effectively and efficiently, so that it can develop into a Disaster-Safe School/Madrasah (SMAB).